New Approach to FFT Algorithms - Barseghyan , Rafayel; Sarukhanyan, Hakob (Mathematical Problems of Computer Science, 2021)
In this paper we present a new, efficient modification of split-radix algorithm for computing a power of two discrete Fourier transforms. The developed algorithm allows to 40% real arithmetic operations reduction in comparison with previous best results for 16-point discrete Fourier transform.